2011
DOI: 10.2514/1.b34167
|View full text |Cite
|
Sign up to set email alerts
|

Annular Diffusers with Large Downstream Blockage Effects for Gas Turbine Combustion Applications

Abstract: ., 2011.Annular diffusers with large downstream blockage effects for gas turbine combustion applications. Journal of Propulsion and Power, 27(6), pp. 1218-1230. Additional Information:• This paper was published in the Journal of Propulsion and In engineering applications, diffuser performance is significantly affected by its boundary conditions. In a gas turbine combustion system, the space envelope is limited, the inlet conditions are generated by upstream turbomachinery, and the downstream geometry is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Walker et al considered the design of an annular diffuser that consists of an outsized downstream obstruction. 11 On a low-speed facility that is provided with compressor-generated inlet conditions and a combustion system simulation, the design was experimentally tested. An integrated design concept was created using an iterative process after due deliberation of the flow field to accommodate the engagement between both the diffuser and flame tube.…”
Section: Introductionmentioning
confidence: 99%
“…Walker et al considered the design of an annular diffuser that consists of an outsized downstream obstruction. 11 On a low-speed facility that is provided with compressor-generated inlet conditions and a combustion system simulation, the design was experimentally tested. An integrated design concept was created using an iterative process after due deliberation of the flow field to accommodate the engagement between both the diffuser and flame tube.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have examined the effect of downstream blockage on the upstream pre-diffuser. For example, the work of Fishenden and Stevens [4], Bailey et al [5] and Walker et al [6] have shown that the pressure field generated by the flame tube can help to stabilize the diffuser flow and enable higher area ratios to be achieved. More recently the work of Impact of a Cooled Cooling Air System on the External Aerodynamics of a Gas Turbine Combustion System Walker et al [7,8] showed that for lean burn combustors the diffuser can be subjected to both circumferential and radial variations of the pressure field by the downstream geometry.…”
mentioning
confidence: 99%